Are Olympians Real Idols of Young People for their Motivation and Participation in Sport? - Antonín Rychtecký (Karolinum Press, 2014)
Are Olympians Real Idols of Young People for their Motivation and Participation in Sport? The aim of this study was to determine: "if Olympic champions are real models and idols for today's young people" and whether they would wish or not to become Olympic champions, and which reasons they associate with their positive or negative answers. 440, 12 and 15 year old respondents participated in surveys carried out in the year 1998 (12 and 15 year old respondents only) and consequently in the period 2010-2011 in which 1274 boys and 1090 girls, 12-19 years, old were respondents in this project. The quota samples were used in the selection of respondents in Prague' and the Central region in the Czech Republic. The parts of the "Olympic Questionnaire", created and verified in the 1998 survey were focused on the analysis of the respondents' answers. The open answers of the respondents were subsequently divided into several general and common categories. The desire to become an Olympic Champion was felt more intensely in respondents of the surveys carried out in the year 1998 than in the project carried out in period 2010-2011. Young people more involved in sports express their wishes to become Olympic winners significantly clearer than those who practice sports seldom or not at all. Over 16 year old respondents are more aware of the difficulties associated with the process of becoming Olympic champions than 12-14 year old pubescent. The evaluation of the differences and identical opinions between the respondents' answers in the observed groups were made by the MANOVA and t-tests for independent samples. The hypothesis about the importance of sports models and idols in current youth was confirmed. The role of Olympic champions is very important; namely in the internalization of the Olympic values in the process of the Olympic education of youth; both at schools and out of schools. Olympians should be aware of the fact that even their behavior which is not related to sport events is noticed by young people. The Olympians should be informed about their influence on young generations. Mass-media play a very important role in their mediation. For these reasons, the collaboration between the Club of Czech Olympians and the Olympic Academy should be innovated. Jsou olympionici skutečnými idoly mládeže v její motivaci a účasti ve sportu? Cílem této studie bylo zjistit: "zda olympijští vítězové jsou reálnými vzory a idoly pro dnešní mladé lidi" a zdali by se chtěli, nebo nechtěli stát olympijskými vítězi, a s jakými důvody jsou asociovány jejich pozitivní či negativní odpovědí. Respondenty a etapy výzkumů. V průzkumu, provedeném v letech 1998 bylo testováno 440 osob ve věku 12 a 15 let. Druhého šetření, v letech 2010-2011, se účastnilo 2364 jedinců, 1274 chlapců a 1090 dívek, ve věku 12 až 19 let dle principů kvótního výběru v Praze a Středočeském kraji, České republiky. Použit byl "Olympijský dotazník" vytvořený a standardizovaný v prvním šetření z roku 1998. Otevřené, volné odpovědi respondentů byly následně rozděleny do několika obecných a společných kategorií. Bylo předpokládáno, že touhu či přání stát se olympijským šampiónem pociťují intenzivněji respondenti z průzkumu provedeného v roce 1998 než v šetření realizovaném v období let 2010-2011. Mladí lidé, kteří se intenzivněji zapojují do sportu, vyjadřuji své přání stát se olympijskými vítězi výrazněji, než osoby méně či vůbec nesportující. Testované osoby starší než 16 let si více uvědomují obtíže spojené s procesem stát se olympijskými vítězi než dospívající ve věku 12-14 let. K statistickému vyhodnocení rozdílů a shodných názorů mezi odpověďmi respondentů ve sledovaných skupinách dle věku a pohlaví respondentů byly použity metody ANOVA, MANOVA a T-testy pro nezávislé vzorky. Výsledky a závěry: hypotéza o významu sportovních vzorů a idolů současné mládeže byla potvrzena. Role olympijských šampionů jsou velmi důležité, zejména v internalizaci olympijských hodnot v procesu olympijské výchovy mládeže. Jak na školách, tak mimo školy. Olympionici by si měli být vědomi skutečnosti, že i jejich chování, které se přímo netýká sportovních událostí, je objektem pozornosti mladých lidí. Olympionici by proto měli být informováni o jejich vlivu na mladou generaci. Masmédia mají velmi důležitou roli v jejich zprostředkování. Z těchto důvodů by měla být spolupráce mezi Klubem českých olympioniků a Olympijskou akademií inovována.